Phytochemical Analysis of a Medicinal Plant Senna Alata (Fabaceae) - Andrianarijaona Mamy; Ralaivaon-Dratsitonta Jumaël Edith Fabrice; Fatiany Pierre Ruphin; Robijaona Rahelivololoniaina Baholy (Britain International of Exact Sciences (BIoEx) Journal, 2025)
A preliminary phytochemical study was conducted on the bark of Senna alata, a medicinal plant widely used in Madagascar, to identify and isolate its chemical constituents. This plant is traditionally used for various ailments, including dermatological and respiratory issues. A sequential solid-liquid extraction with solvents of increasing polarity—hexane, dichloromethane (DCM), and ethanol—was performed, with the polar ethanol extract yielding the highest mass. Phytochemical screening of the hydroethanolic extract confirmed the presence of several compound classes. Abundant polysaccharides and flavonoids were detected, along with low concentrations of alkaloids, steroids, saponins, and polyphenols. The DCM extract was then subjected to column chromatography, with fractions monitored by thin-layer chromatography (TLC), which was also used to optimize the solvent system for separation. This process isolated two pure fractions, F28-34 and F61-69. The more abundant fraction, F61-69 (8 mg), was selected for structural elucidation. Mass spectrometry revealed a molecular ion peak at m/z 400, establishing the compound's molecular weight. Subsequent analysis by 1H NMR and 13C NMR spectroscopy revealed a characteristic steroid skeleton. The compound contains 28 carbons and its Double Bond Equivalence (DBE) was calculated as 5, corresponding to four rings and one double bond. Based on the comprehensive spectroscopic data and a comparison to literature, the compound was definitively identified as Campesterol.